Treatment engagement of people in forensic personality disorder services - Wyse, Kate (2016)
This thesis explores the contribution of the Personal Concerns Inventory (PCI; Cox & Klinger, 2000) to the development of treatment engagement strategies with people with personality disorder (PD) in forensic settings. A systematic literature review of evaluated engagement strategies with offenders and people with PD showed little diversity in terms of strategies evaluated with PD, specifically psycho-education and goal-based interventions only (Chapter 2). Furthermore current literature focuses mainly on motivational interviewing (MI) in offenders as somewhat useful in increasing motivation to engage and change. However preliminary support for node-mapping and interactive activities has been found in a small number of studies. The distinct lack of strategies with PD is problematic considering the high treatment non-completion rates with this population and the case study in Chapter 3 discusses the complexity of working with patients with PD. It finds Dialectical Behaviour Therapy (DBT), which embeds motivational strategies in its programme, as improving not only treatment retention but also clinical outcomes, thereby offering further encouragement in focusing engagement strategies with PD. Consequently, a critique of the PCI was necessary in understanding the PCI as both a measure of motivation to change and a motivational intervention. This semi-structured interview demonstrates reasonable reliability and validity however the offender variants’ psychometric properties are weaker. The robust theoretical basis of the PCI and the consistent positive qualitative feedback from participants suggests value in evaluating the tool as a motivational intervention. Thus Chapter 5, an empirical study, evaluates the PCI followed by goal counselling as a motivational intervention with people with PD using a mixed-methods approach and a small number multiple baseline design. The quantitative results offer limited support for the effectiveness of the PCI or understanding of the process of change. However the qualitative data reflects that in existing PCI literature: participants perceived it as effective in focusing them on their goals and the relevance of treatment, thereby enhancing motivation. Therefore further investigations are needed to clarify discrepancies between participant perception and the outcome measure data in order to understand the extent to which the PCI enhances motivation.